2008
DOI: 10.1007/s00239-007-9040-x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary and Epidemiological Dynamics of the Paramyxoviridae

Abstract: Paramyxoviruses are responsible for considerable disease burden in human and wildlife populations: measles and mumps continue to affect the health of children worldwide, while canine distemper virus causes serious morbidity and mortality in a wide range of mammalian species. Although these viruses have been studied extensively at both the epidemiological and the phylogenetic scales, little has been done to integrate these two types of data. Using a Bayesian coalescent approach, we infer the evolutionary and ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
67
6
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 27 publications
18
67
6
1
Order By: Relevance
“…In addition, the genetic diversity found within the different sublineages of HMPV was of a very recent origin, and HMPV as a whole was characterized by low levels of standing genetic variation (as reflected in estimates of N e t). Such limited genetic diversity, which is also characteristic of human influenza A virus (Rambaut et al, 2008), as well as other paramyxoviruses (Pomeroy et al, 2008) is most likely due to repeated (annual) population bottlenecks, which periodically purge genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the genetic diversity found within the different sublineages of HMPV was of a very recent origin, and HMPV as a whole was characterized by low levels of standing genetic variation (as reflected in estimates of N e t). Such limited genetic diversity, which is also characteristic of human influenza A virus (Rambaut et al, 2008), as well as other paramyxoviruses (Pomeroy et al, 2008) is most likely due to repeated (annual) population bottlenecks, which periodically purge genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis performed on different genes showed MV and RPV to be the closest viruses within morbilliviruses (Diallo et al, 1994;Minet et al, 2009). However to shed light on the evolutionary history of morbilliviruses, Bayesian coalescence approaches have been used to estimate the phylogenetic split that occurred among the ancestral viruses of MV and RPV (Pomeroy et al, 2008;Furuse et al, 2010) and to put a new perspective on PPRV modern evolution as reported in a recent analysis by Muniraju et al (2013).…”
Section: Origin Of Pprvmentioning
confidence: 98%
“…Evolutionary history leading to the diversity now shown for PPR was a relative fast phenomenon. As a comparison, the diversity of the MV may have emerged in humans within the last 70 years, an even more recent episode (Pomeroy et al, 2008).…”
Section: Origin Of Pprvmentioning
confidence: 99%
“…Canine distemper virus (CDV), a paramyxovirus of the genus Morbillivirus, was first described in 1905 (48). CDV most commonly affects dogs and causes gastrointestinal and respiratory symptoms as well as neurological symptoms.…”
mentioning
confidence: 99%